2004
DOI: 10.1101/gad.1227804
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate receptor regulation of N-cadherin mediates vascular stabilization

Abstract: [Keywords: sphingosine 1-phosphate; cadherin; angiogenesis; vascular stabilization; endothelial cells; pericytes] Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
190
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(202 citation statements)
references
References 64 publications
(65 reference statements)
12
190
0
Order By: Relevance
“…PP protrusions S1pr1 in MKs controls PPF. As reported previously for endothelial cells (Paik et al, 2004), we found that S1P, and also the S1pr1-specific agonist SEW2871, enhances Rac GTPase activity via S1pr1 in megakaryocytic cell lines (Fig. 4,E and F).…”
Section: S1pr1 Is Essential For Intravascular Pp Formation (Ppf)supporting
confidence: 65%
“…PP protrusions S1pr1 in MKs controls PPF. As reported previously for endothelial cells (Paik et al, 2004), we found that S1P, and also the S1pr1-specific agonist SEW2871, enhances Rac GTPase activity via S1pr1 in megakaryocytic cell lines (Fig. 4,E and F).…”
Section: S1pr1 Is Essential For Intravascular Pp Formation (Ppf)supporting
confidence: 65%
“…The intermediary pathways that allow SphK2 to regulate the expression and localization of the junctional proteins at the BBB have yet to be clarified, but it would not be unexpected if SphK2-derived S1P signaling proceeded via mediators and pathways already known to regulate BBB tight junctions and/or BBB permeability, such as nitric oxide, vascular endothelial growth factor, proteases, and reactive oxygen species, as well as the actin cytoskeleton, caveolae, and pericytes (Sandoval and Witt, 2008). Indeed, there is evidence from studies in the peripheral vasculature that S1P activates endothelial nitric oxide synthase via PI3K/ Akt, counteracts the deleterious effects of reactive oxygen species on vascular endothelium via ERK1/2 and endothelial nitric oxide synthase (Igarashi and Michel, 2008), and regulates pericyte recruitment via N-cadherin signaling (Paik et al, 2004). Sphingosine-1-phosphate R1 receptor activation also induces intracellular calcium release from the endoplasmic reticulum and Rac-1 activation, promoting adherens junction formation at the endothelial cell periphery that can block vascular endothelial growth factorinduced vascular permeability (Hoang et al, 2011;Mehta et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…S1P 1 activation enhances the recruitment of pericytes to remodeling vessels (6,34). Recent evidence by Stark et al identifies interactions between arterial pericytes and CX3CR1 + monocytes during inflammation (32), which may suggest that pericytes play multiple roles in regulation of vascular and inflammatory modulation.…”
Section: Discussionmentioning
confidence: 99%